Analysis of the Status and Future Direction for Digital Therapeutics in Children and Adolescent Psychiatry - Choi, Haemi; Kim, Bora; Kim, Insoo; Kang, Jae-Gu; Lee, Yoonjae; Lee, Hyowon; Park, Min-Hyeon (Journal of korean Academy of Child and Adolescent Psychiatry, 2023)
Digital therapeutics based on software, such as artificial intelligence, virtual reality, games, and smartphone applications, are in the spotlight as new therapeutic alternatives in child and adolescent psychiatry. It draws attention to overcoming conventional therapeutics' limitations, such as toxicity, cost, and accessibility, and encourages patients to participate in the treatment attractively. The growth potential of the digital therapeutics market for psychiatric disorders in children and adolescents in Korea and abroad has been highlighted. Clinical studies and Food and Drug Administration approvals for digital therapeutics have increased, and cases approved by the Ministry of Food and Drug Safety have emerged in Korea. As seen above, digital transformation in child and adolescent psychiatry will change treatment paradigms significantly. Therefore, as this new field has just begun to emerge, it is necessary to verify the effectiveness and scope of the application of digital therapeutics and consider preparing a compensation system and institutional arrangements. Accordingly, this study analyzed the development trends and application status of digital therapeutics in children and adolescents and presented limitations and development directions from the perspective of application in healthcare. Further, the study is expected to identify the utility and limitations of digital therapeutics for children and adolescents and establish effective application measures.